Trends in psychological distress and alcoholism after The Great East Japan Earthquake of 2011 - A. Kanehara; S. Ando; T. Araki; S. Usami; H. Kuwabara; Y. Kano; K. Kasai (Elsevier, 2016)
Aims: Many studies have shown that natural disasters affect mental health; however, longitudinal data on post-disaster mental health problems are scarce. The aims of our study were to investigate the trend in psychological distress and alcoholism after The Great East Japan Earthquake and tsunami in north eastern Japan, in March 2011. Methods: A longitudinal study was conducted using annual health check data for the general population, in the city of Higashi-Matsushima, which was affected by the high impact of tsunami. In 2012 and 2013, the Kessler Psychological Distress Scale and the CAGE questionnaire (for screening for alcoholism) were used to assess psychological distress and prevalence of alcoholism. Results: Of 11,855 total eligible residents, 2192 received the annual check in 2012 and 2013. The prevalence of mental illness and the mean score of alcoholism tendency increased during the follow-up period. The majority of respondents (43.8%) with baseline serious mental illness (SMI) continued to have SMI at follow-up; only 16.7% reported recovering. Older age, female sex, and severity of home damage predicted higher psychological distress, while male sex was a risk factor for alcoholism at follow-up. Conclusions: Psychological distress deteriorated 2 years after the huge natural disaster, compared with 1 year after the disaster. Long-term mental health care is needed for those affected by natural disasters, particularly those who have suffered loss. Keywords: Natural disaster, Psychological distress, Alcoholism, Longitudinal study